Ambulatory electrocardiographic ST segment changes in healthy volunteers. - Quyyumi, A A (1983)
Twenty four hour ambulatory monitoring was performed on 120 healthy volunteers using a frequency modulated recorder: 50 men and 50 women below 40 years and 20 men between 40 and 60 years were studied. Twenty eight subjects had episodes of ST segment elevation (range 1-3 mm), which occurred almost invariably at night with a slow heart rate 62.4 +/- 10.4 beats/min). ST segment elevation occurred most often in men, and was not found in subjects over the age of 37. Also in 10 subjects horizontal or downsloping ST segment depression (range 1-2 mm) was recorded, usually in association with tachycardia (135 +/- 10.5 beats/min). Nine of these exercised on a bicycle ergometer, and widespread ST segment depression was observed in eight. Thus ST segment changes, which are often interpreted as myocardial ischaemia in patients with ischaemic heart disease, are commonly seen in 24 hour electrocardiographic monitoring of healthy volunteers.